Study on carbonation corrosion mechanism and hydration of phosphoaluminate cement for CCUS wells - Yuan, Bin; Zhang, Xingyang; Yang, Shuo; Xu, Bihua; Zheng, Zehao (Geoenergy Science and Engineering, 2025)
Phosphoaluminate cement (PAC) known for its superior corrosion resistance and mechanical properties, emerges as a promising material for cementing in Carbon capture utilization and storage (CCUS) wells. Therefore, this paper simulated the conditions of 90 °C, 8 MPa CO2 partial pressure and 20 MPa formation pressure, analyzed the macroscopic properties and microstructure of PAC before and after corrosion by using the compressive strength test, permeability test, scanning electron microscope (SEM), X-ray diffraction (XRD) and other technological means. The results showed that, with the development of hydration time, the compressive strength of PAC first increased and then decreased, and the permeability first decreased and then increased; its main hydration products were hydrated PAC gel (CAP) and calcium aluminate (CA), and its microstructure evolved from floral to columnar and blocky gels. After corrosion, the compressive strength of the corroded 14d cement samples increased by 5.9 %, and the permeability increased by 82.5 %. The CO2 corrosion accelerated the hydration process of the hydration products CAP and CA, which led to the transformation of CAP and CA microstructure into 3CaO-Al2O3-6H2O (C3AH6) spherical gel. In addition, the carbonation corrosion process of PAC is divided into the dissolution process, induction process, carbonation process, decomposition process and dissolving corrosion process according to stages. Its carbonation corrosion mechanism: hydroxyapatite produced by hydration of PAC can absorb CO2 to generate CaCO3, Ca10(PO4)6CO3 and soluble Ca3(PO4)2 and other products. •The corrosion mechanism of phosphoaluminate cement was investigated.•Carbonation corrosion accelerates phosphoaluminate cement hydration and micromorphology transformation.•CaCO3 combined with C3AH6 to improve the mechanical properties of phosphoaluminate cement.